Rapid Deprotection of O-Allyoxycarbonyl(alloc) Alcohols by NiCl2•6H2O and NaBH4 - Yuan, Xinxin; Zeng, Qian-Ding; Yao, Hongmiao; Jin, Wenjun; Ren, Jiangmeng; Zeng, Bu-Bing (Synlett, 2025)
A novel protocol for the deprotection of the O-allyloxycarbonyl(alloc) group by nickel(II) chloride hexahydrate with sodium borohydride in acetone at 0 °C to give the corresponding parent alcohols and phenols in high yields was demonstrated. This method had the advantages of mild reaction conditions and broad substrate scope. The deprotection had also been validated in gram scale, to establish the appropriateness of this protocol.
Keywords: Deprotection; O-Allyloxycarbonyl; Nickel(II) chloride hexahydrate; Sodium borohydride; Broad substrate scope